ظفر الحق چشتی کی مذہبی شاعری کا تجزیاتی مطالعہ: قرآن و حدیث اورعربی شاعری کے تناظر میں - Sarwar, Dr. Muhammad Awais (Zoraiz, 2022)
Arab poets are credited with the origin of the art of Na’at, so there has always been a reflection or impression of the Arabic language and poetry in the subjects and styles of Urdu poetry. Zafarul Haq Chishti is one of those poets whose poetry has deep influences of Arabic language and literature .After examining his poetry and especially Na’atia poetry, it is clear that the Arabic language and literature have had a profound impact on his poetry, thoughts and style of speech. The deep influence of Arabic language and literature makes his poetry very important and useful among the students and researchers who love Urdu and Arabic literature. His poetry is not only a treasure of profound themes and varied vocabulary, but also a shining example of poetic maturity and creative craftsmanship.